The Southern Literary Messenger, Vol. II., No. 12, November, 1836 - Various; Poe, Edgar Allan, 1809-1849 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Southern Literary Messenger, Vol. II., No. 12, November, 1836" by Various is a literary periodical written in the early 19th century. This publication features a diverse assemblage of essays, poetry, commentary, literary criticism, and serialized fiction, with contributions from multiple authors. The contents range from reflective poems and philosophical essays to vivid stories and critical examinations of historical and literary figures, aimed at engaging readers interested in literature and the arts. Its likely audience includes those who appreciate thought-provoking discussions on friendship, history, classical philosophy, as well as original creative writing and tales inspired by American landscapes and history. The opening of this volume presents a rich mosaic of genres and topics: it begins with contemplative poetry about the soul$1 (Bs retreat from worldly turmoil, shifts into an amusing personal account of the changes in modern travel, and follows with an essay exploring the nature and virtues of friendship. Other early selections include literary reflections sparked by a biblical seal, a prose analysis of Coriolanus$1 (Bflawed character, lively verse about the belles of Williamsburg, and a brief survey of ancient philosophy$1 (Bs roots. The section concludes with the start of a serialized adventure titled "The Kidnapper$1 (Bs Cove," which unfolds an American frontier tale blending themes of indigenous life, family, loyalty, and betrayal. This variety showcases the periodical$1 (Bs commitment to breadth and depth, promising intellectual engagement and entertainment for readers with eclectic literary tastes. (This is an automatically generated summary.)s
Release date is 2025-04-01
Ron Swanson
Keywords: American literature -- 19th century -- Periodicals